Intergenerational ambivalence among Mexican American families. Issue 3 (3rd July 2019) - Pei, Yaolin; Cong, Zhen
ABSTRACT: This study examined correlates of Mexican American older parents' ambivalent feelings toward each of their child. Especially we investigated how children's characteristics including their gender, social achievements measured by education and marital status, as well as intergenerational solidarity measured by contact and financial exchanges with their older parents, were associated with intergenerational ambivalence. The sample included 341 parent–child pairs nested within 94 older parents. Two-level mixed-effects models were used to examine the research questions. We found that although children's education did not have a main effect on intergenerational ambivalence, parents felt stronger ambivalence toward a son when he had a lower level of education. Parents also had higher levels of ambivalence toward those children who were unmarried and who had lower levels of contact with parents. The greater the financial support to adult children, the greater the intergenerational ambivalence older parents felt toward those children. The findings highlight the importance of linking the larger social and cultural contexts to individuals in the research on intergenerational ambivalence.